2013
DOI: 10.1149/2.021307jes
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Electrochemically Induced DNA Damage Using Capillary Electrophoresis

Abstract: Exposure of mammalian cells to oxidative stress can result in DNA damage that adversely affects many cell processes. We used bulk electrolysis in an electrochemical system and capillary electrophoresis (CE) to control and measure the effect of oxidative stress on DNA. Calf thymus DNA and a fluorescently labeled DNA sizing ladder were subjected to fixed oxidizing potentials using a reticulated vitreous carbon electrode (RVC) and their fragmentation was measured with the use of CE. The resulting electropherogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A BDD working electrode (WE) was utilized to establish a stable oxidizing environment, an environment whereby DNA samples with quantifiable levels of oxidatively modified lesions could be produced. Previously, with capillary electrophoresis, we have quantified nucleic acid fragmentation under a constant oxidizing potential treatment using a reticulated carbon WE [ 36 ]. Here we equilibrate solution-state DNA with a high surface area BDD WE, biased at constant potentials in the range from 0.5 V to 2.0 V. When polarized at 2V the BDD electrode becomes an efficient • OH radical producer while limiting oxygen evolution due to its high overpotential [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A BDD working electrode (WE) was utilized to establish a stable oxidizing environment, an environment whereby DNA samples with quantifiable levels of oxidatively modified lesions could be produced. Previously, with capillary electrophoresis, we have quantified nucleic acid fragmentation under a constant oxidizing potential treatment using a reticulated carbon WE [ 36 ]. Here we equilibrate solution-state DNA with a high surface area BDD WE, biased at constant potentials in the range from 0.5 V to 2.0 V. When polarized at 2V the BDD electrode becomes an efficient • OH radical producer while limiting oxygen evolution due to its high overpotential [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…e concentration of hydrogen peroxide is particularly difficult to quantify, primarily due to its instability in storage and in cellular media, (8-hydroxyguanine, 8-hydroxyadenine and 5-hydroxy-5-methylhydantoin) were produced during electrochemical treatment at 퐸 = 2.0 V for 1 h [16]. Also, in an earlier study, using capillary electrophoresis, we found extensive strand breakage in calf thymus DNA when exposed for 1 h at 퐸 = 3.0 V and in Poly A and Poly G nucleotides exposed 1 h at 퐸 = 1.0 V [21]. ese studies show that the production of significant DNA damage under physiological conditions in this electrode potential range is consistent with our current studies of mammalian cells.…”
Section: Discussionmentioning
confidence: 54%
“…Various instrumental techniques such as electrophoresis [16, 17, 18], high-performance liquid chromatography (HPLC) [19, 20, 21], photoelectrochemical methods [22, 23, 24] and fluorescence methods [25, 26, 27] have been reported for detection of DNA damage. Despite their sensitivity, these methods have some disadvantages such as complexity, long assay time, high cost and labor-intensive.…”
Section: Introductionmentioning
confidence: 99%